Effect Of Dietary Lipid Level On Growth, Feed Utilization And Body Composition By Nile Perch Juveniles (Lates Niloticus) - Amadou, Ly Mouhamadou; Tidiane, Ba Cheikh (European Scientific Journal, ESJ, 2016)
The present study was designed to determine the optimum dietary lipid of juveniles Nile perch for better growth performances. Four isonitrogenous (45 %) experimental diets were formulated to contain 9; 11; 13 and 15 g crude lipid 100 g-1 feed, and fed in triplicate groups of Nile perch (mean weight : 3.28 Â± 0.04 g) reared in twelve 50 L tank for 8 weeks. At the end of the experimental period the group of fish fed 11 % and 9 % lipid, had a significantly higher SGR and body weight gain than the rest of experimental groups. The lowest body weight (13.28 g) was achieved by group of fish fed 15 % lipid. The FCR were significantly lower for fingerling Lates fed diet containing 11 % and 9 % lipid than the rest. The increase of the dietary lipid level in the diet affected significantly the Protein Efficiency Ratio (PER). Body moisture content decreased significantly with the increase of dietary lipid. Body lipid increased significantly with the increase of dietary lipid. Under the experimental conditions applied, the optimum dietary lipid requirement for juvenile Lates niloticus is estimated to be 9.79 %.